The Forward-Backward Method
Download
Report
Transcript The Forward-Backward Method
The Forward-Backward
Method
The First Method To Prove
If A, Then B.
The Forward-Backward Method
General Outline (Simplified)
Recognize
the statement “If A, then B.”
Use the Backward Method repeatedly until A is
reached or the “Key Question” can’t be asked or
can’t be answered.
Use the Forward Method until the last statement
derived from the Backward Method is obtained.
Write the proof by
– starting with A, then
– those statements derived by the Forward Method, and then
– those statements (in opposite order) derived by the Backward
Method
An Example:
If the right triangle XYZ with sides of lengths x and y,
and hypotenuse of length z, has an area of z2/4, then
the triangle XYZ is isosceles.
• Recognize the statement “If A, then B.”
A: The right triangle XYZ with sides of lengths x and y,
and hypotenuse of length z, has an area of z2/4.
B: The triangle XYZ is isosceles.
The Backward Process
Ask
the key question:
“How can I conclude that statement B is true?”
– must be asked in an ABSTRACT way
– must be able to answer the key question
– there may be more than one key question
» use intuition, insight, creativity, experience, diagrams, etc.
» let statement A guide your choice
» remember options - you may need to try them later
Answer
the key question.
Apply the answer to the specific problem
– this new statement B1 becomes the new goal to prove from
statement A.
The Backward Process: An Example
Ask
the key question: ‘How can I conclude that
statement :
“The triangle XYZ is isosceles” is true?’
– ABSTRACT key question:
“ How can I show that a triangle is isosceles?”
Answer the key question.
– Possible answers: Which one? ... Look at A: The right triangle
XYZ with sides of lengths x and y, and hypotenuse of length z,
has an area of z2/4
» Show the triangle is equilateral.
» Show two angles of the triangle are equal.
» Show two sides of the triangle are equal.
Apply
–
the answer to the specific problem
New conclusion to prove is B1: x = y.
– Why not x = z or y = z ?
Backward Process Again:
Ask
the key question: ‘How can I conclude that
statement :
“B1: x = y” is true?’
– ABSTRACT key question:
“ How can I show two real numbers are equal?”
Answer the key question.
– Possible answers: Which one? ... Look at A.
» Show each is less than and equal to the other.
» Show their difference is 0.
Apply
–
the answer to the specific problem
New conclusion to prove is B2: x - y = 0.
Backward Process Again:
Ask
the key question: ‘How can I conclude that
statement :
“B2: x - y = 0” is true?’
ABSTRACT
key question:
No reasonable way to ask a key
question. So,
Time to use the Forward Process.
The Forward Process
From
statement A, derive a conclusion A1.
– Let the last statement from the Backward Process guide you.
– A1 must be a logical consequence of A.
If A1
is the last statement from the Backward
Process then the proof is complete,
Otherwise use statements A and A1 to derive a
conclusion A2.
Continue deriving A3, A4, .. until last statement
from the Backward Process is derived.
Variations of the Forward Process
A derivation
might suggest a way to ask or answer
the last key question from the Backward Process;
continuing the Backward Process.
An alternative question or answer may be made for
one of the steps in the Backward Process;
continuing the Backward Process from that point
on.
The Forward-Backward Method might be
abandoned for one of the other proof methods
The Forward Process: Continuing
the Example
Derive
from statement A: The right triangle XYZ
with sides of lengths x and y, and hypotenuse of
length z, has an area of z2/4.
–
–
–
–
–
–
–
A1: ½ xy = z2/4
(the area = the area)
A2: x2 + y2 = z2
( Pythagorean theorem)
A3: ½ xy = (x2 + y2)/4
( Substitution using A2 and A1)
A4: x2 -2xy + y2 = 0
( Multiply A3 by 4; subtract 2xy )
A5: (x -y)2 = 0
( Factor A4 )
A6: (x -y) = 0
( Take square root of A5)
Note: A6 B2, so we have found a proof
Write the Proof
Statement
A:
Reason
The right triangle XYZ with sides of lengths x and y, and
hypotenuse of length z, has an area of z2/4.
Given
A1: ½ xy = z2/4
Area = ½base*height; and A
A2: x2 + y2 = z2
Pythagorean theorem
A3: ½ xy = (x2 + y2)/4
Substitution using A2 and A1
A4: x2 -2xy + y2 = 0
Multiply A3 by 4; subtract 2xy
A5: (x -y)2 = 0
Factor A4
B2: (x -y) = 0
Take square root of A5
B1: x = y
Add y to B2
B: XYZ is isosceles
B1 and definition of isosceles
Write Condensed Proof - Forward
Version
From the hypothesis and the formula for the area of
a right triangle, the area of XYZ = ½ xy = ¼ z2. By
the Pythagorean theorem, (x2 + y2) = z2, and on
substituting (x2 + y2) for z2 and performing some
algebraic manipulations one obtains (x -y)2 = 0.
Hence x = y and the triangle XYZ is isosceles.
Write Condensed Proof - Forward
& Backward Version
The statement will be proved by establishing that x =
y, which in turn is done by showing that (x -y)2 =
(x2 -2xy + y2) = 0. But the area of the triangle is
½ xy = ¼ z2, so that 2xy = z2. By the Pythagorean
theorem, x2 + y2 = z2 and hence (x2 + y2) = 2xy, or
(x2 -2xy + y2 ) = 0.
Write Condensed Proof Backward Version
To reach the conclusion, it will be shown that x = y
by verifying that (x -y)2 = (x2 -2xy + y2) = 0, or
equivalently, that (x2 + y2) = 2xy. This can be
established by showing that 2xy = z2, for the
Pythagorean theorem states that (x2+y2) = z2. In
order to see that 2xy = z2, or equivalently, that ½ xy
= ¼ z2, note that ½ xy is the area of the triangle and
it is equal to ¼ z2 by hypothesis, thus completing
the proof.
Write Condensed Proof - Text Book
or Research Version
The hypothesis together with the Pythagorean
theorem yield (x2 + y2) = 2xy; hence (x -y)2 = 0.
Thus the triangle is isosceles as required.
Another Forward-Backward Proof
Prove: The composition
of two one-to-one
functions is one-to-one.
Recognize
the statement as “If A, then B.”
Recognize as “If A, then B.”
If
f:XX and g:XX are both one-to-one
functions, then f o g is one-to-one.
A:
The functions f:XX and g:XX are both oneto-one.
B: The function f o g: XX is one-to-one.
What
is the key question and its answer?
The Key Question and Answer
Abstract
question
How do you show a function is one-to-one.
Answer:
Assume that if the functional value of
two arbitrary input values x and y are equal then x
= y.
Specific answer B1: If f o g ( x ) = f o g ( y ), then x = y.
How
do you show B1? What is the key question?
The Key Question and Answer
How
do you show
B1: If f o g ( x ) = f o g ( y ), then x = y.
Answer:
We note that B1 is of the form If A`, the B`, and
use the Forward-Backward method to prove the
statement
If A and A`, then B`. ie.,
If the functions f:XX and g:XX are both
one-to-one functions and if f o g ( x ) = f o g ( y ),
then x = y.
So we begin with B` : x = y and note that, since we
don’t know anything about x & y except that x & y
are in the domain X, we can’t pose a reasonable
key question for B` so we should begin the Forward
Process for this new if-then statement.
The Forward Process
A`:
The functions f:XX and g:XX are both
one-to-one functions and f o g ( x ) = f o g ( y )
A`1: f(g(x)) = f(g(y))
(definition of composition)
A`2: g(x) = g(y)
(f is one-one)
A`3: x = y
(g is one-one)
Note that A`3 is B` so we have proved the statement
Now write the proof.
Write the Proof
Statement
A:
The functions f:XX
and g:XX are both
one-to-one.
A`: f o g ( x ) = f o g ( y )
A`1: f(g(x)) = f(g(y))
A`2: g(x) = g(y)
A`3: x = y
B:
f o g is 1-1
Reason
Given
Assumed to prove f o g is 1-1
definition of composition
f is 1-1 by A
g is 1-1 by A
definition of 1-1
Condensed Proof
Suppose the f:XX and g:XX are both one-to-one.
To show f o g is one-to-one we assume f o g ( x ) = f o g ( y ).
Thus f(g(x)) = f(g(y) and since f is one-to-one, g(x) = g(y).
Since g is also one-to-one x = y.
Therefore f o g is one-to-one.